UPAYA MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL INTERAKTIF BERBASIS AKTIVITAS PADA SISWA KELAS V SDN 104/IX KEDEMANGAN - Jamalia, Jamalia (Universitas Slamet Riyadi, 2018)
Elementary school number 104 / IX kademangan set KKM science subjects class V of 65 with the provisions of 100% complete, still very many students who have not reached completeness, the purpose of this research is to increase learning outcome in science subjects in class V. This research is a classroom action research conducted in three cycles with two learning meetings, which includes: planning, implementation, and reflection, Sixteen study subjects consisted of nine males and eight females, Data collection techniques used a written assessment, observations in the form of indicators of teacher and student success, the results showed that on the pre cycle of percentage of student learning outcomes that is 24%, in the first cycle increased by a percentage 76%, then in the second cycle is 100% complete with the highest 85, the lowest 80, and the average 82,81. Based on these results, it can be concluded that the activity-based interactive model can improve the learning outcomes of grade V students in science subjects at elementary school number 104 / IX Kedemangan.